A coupled thermo-hydro-mechanical finite element formulation of one-dimensional beam elements for three-dimensional analysis. (December 2018) - Gawecka, Klementyna A.; Potts, David M.; Cui, Wenjie; Taborda, David M.G.; Zdravković, Lidija
Abstract: Finite element (FE) analysis in geotechnical engineering often involves entities which can be represented as one-dimensional elements in three-dimensions (e.g. structural components, drains, heat exchanger pipes). Although structural components require an FE formulation accounting only for their mechanical behaviour, for the latter two examples, a coupled approach is necessary. This paper presents the first complete coupled thermo-hydro-mechanical FE formulation for one-dimensional beam elements for three-dimensional analysis. The possibility of deactivating each of the systems enables simulation of both coupled and uncoupled behaviour, and hence a range of engineering problems. The performance of these elements is demonstrated through various numerical simulations.